Students' Fear After Columbine: Findings from a Randomized Experiment - Addington, Lynn A. (Journal of quantitative criminology, 2003)
On April 20, 1999, the most deadly act of school violence in the United States occurred at Columbine High School. Public perceptions and media accounts suggested that fear of victimization at school greatly increased after Columbine. The actual response is unknown. The 1999 School Crime Supplement to the National Crime Victimization Survey provides a unique opportunity to study Columbine's effect on students' fear. Experimental conditions were approximated by the NCVS sampling design that randomly allocated the 12- to 18-year-old student-respondents to pre- and post-April 20 groups. Contrary to expectations, students were only slightly more fearful after Columbine. An initial explanation for this finding is explored. As little is known about fear following highly publicized incidents of extreme violence such as Columbine and the terrorist attacks of September 11, 2001, this research provides an essential foundation for further study and theoretical development in this largely-ignored area of fear.